Isolation of Campylobacter fetus subsp. venerealis from seminal vesicle of a naturally challenged bull - García, Juan Agustín (2021)
Campylobacter fetus is a well-recognized pathogen that affects reproductive rate in cattle. In the present study, two Angus bulls were kept (39 days) separately with a group of heifers experimentally infected withCampylobacter fetus subsp.venerealis (Cfv) andCampylobacter fetus subsp.venerealis biovarintermedius (Cfvi), respectively. Each bull resulted infected post-mating by its respective strain (Cfv andCfvi). Semen samples collected from each bull at days 39, 82, 132 and 269 resulted positive forC. fetus by bacteriological culture and/or direct immunofluorescence (DIF) test, and confirmed by polymerase chain reaction (PCR) from colonies isolated. Diagnosis resulted better with bacteriological culture (100%) compared to DIF (37,5%).Campylobacter fetus was isolated from seminal vesicle and preputial mucosa by bacteriological culture and confirmed by PCR and DIF test from colonies previously isolated from these tissues (day 276). Microscopic lesions detected in both bulls showed moderate diffuse subepithelial lymphoplasmacytic postitis. None of the seminal vesicle presented relevant microscopic lesions. To our knowledge this is the first report of isolation ofC. fetus from seminal vesicles in a bull. The experimental model herein described, mimicks the natural infection and constitutes a promising alternative for future studies of campylobacteriosis in cattle.